2016
DOI: 10.5812/ircmj.22052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disorders Among Children 4 - 6 Years Old in Tehran Province, Iran

Abstract: BackgroundSleep patterns may change over a person’s lifetime; however, the quantity and quality of sleep always depend on individual factors such as age, sex, and psychological and environmental factors. In children, sleep is as important as development. Quantitative sleep problems related to sleep onset and qualitative sleep disorders such as frequent awakenings may lead to insufficient sleep.ObjectivesThis study aimed to assess the prevalence of sleep disorders among children 4 - 6 years old attending the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…In the current study, we observed no significant difference in the prevalence of sleep disorders between the age groups of 5 -8 and 9 -12 (P = 0.739), which was in opposed to the findings of Ozgoli et al, who reported a rise in the prevalence of sleep disorders with advancing age towards 68 months (i.e., six years old) and above (22). Moreover, in the study of Mohsenzadeh et al, the prevalence of sleep talking increased with age; nevertheless, other sleep disorders did not show a significant relationship with age (21).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, we observed no significant difference in the prevalence of sleep disorders between the age groups of 5 -8 and 9 -12 (P = 0.739), which was in opposed to the findings of Ozgoli et al, who reported a rise in the prevalence of sleep disorders with advancing age towards 68 months (i.e., six years old) and above (22). Moreover, in the study of Mohsenzadeh et al, the prevalence of sleep talking increased with age; nevertheless, other sleep disorders did not show a significant relationship with age (21).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, in another study in Iran, Ozgoli et al assessed 400 children aged 4 -6 and reported a relatively higher rate of sleep disorders (63.25%) than in previous studies. In a recent study, behavioral sleep disorders (13%), nocturnal awakening disorders (37.5%), morning awakening disorders (45.25%), and daytime sleep disorders (14.5%) were reported to be at moderate to severe levels (22).…”
Section: Discussionmentioning
confidence: 96%
“…In a study by van Listenburg et al ( 2010) 21 in the Netherlands, the average disorder in the children sleeping habits was 40.50 ± 0.59 and the most common disorder was related to daily sleepiness habits (1. In Iran, the results of Ozgoli et al (2016) showed that 63.25% of children had moderate to severe sleep disorders, 64.9% had disorder in the morning awakening and 28.9% had disorder in sleep behavior 22 . Khazaie et al (2013) mentioned sleep disorder and especially sleep resistance of 20.5% as the most inappropriate children's sleep habits 23 .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effect of the carnosine treatment on sleep disorders of the participants, Iranian version of Children's Sleep Habits Questionnaire (CSHQ) was used at the beginning and end of the intervention. This tool was previously validated using content validity, and its internal consistency was used at 0.82 Cronbach's a coefficient for the total scale [23]. It is a retrospective sleep screening instrument with 33 items and eight subscales which reflect key sleep scopes identifying the main sleep problems.…”
Section: Primary Outcome Of the Interventionmentioning
confidence: 99%